University of Antioquia Nursing Faculty: sixty years setting a path in the professional training - Castañeda Montoya, Mabel; Pérez Peláez, Liria (Investigación y Educación en Enfermería, 2010)
A journey through the main contributions that the nursing school directors and then the Faculty deans have had in sixty years of professional training history is presented in this article.